Interferon-gamma-activated macrophages infected with Burkholderia cenocepacia process and present bacterial antigens to T-cells by class I and II major histocompatibility complex molecules - Roberto Rosales-Reyes; Paola Garza-Villafuerte; Daniela Vences-Vences; Daniel F. Aubert; Rubi Aca-Teutle; Vianney F. Ortiz-Navarrete; Laura C. Bonifaz; Julio Cesar Carrero-Sánchez; Alfonso Olivos-García; Miguel A. Valvano; José Ignacio Santos-Preciado (Emerging Microbes and Infections, 2020)
ABSTRACTBurkholderia cenocepacia is an emerging opportunistic pathogen for people with cystic fibrosis and chronic granulomatous disease. Intracellular survival in macrophages within a membrane-bound vacuole (BcCV) that delays acidification and maturation into lysosomes is a hallmark of B. cenocepacia infection. Intracellular B. cenocepacia induce an inflammatory response leading to macrophage cell death by pyroptosis through the secretion of a bacterial deamidase that results in the activation of the pyrin inflammasome. However, how or whether infected macrophages can process and present B. cenocepacia antigens to activate T-cells has not been explored. Engulfed bacterial protein antigens are cleaved into small peptides in the late endosomal major histocompatibility class II complex (MHC) compartment (MIIC). Here, we demonstrate that BcCVs and MIICs have overlapping features and that interferon-gamma-activated macrophages infected with B. cenocepacia can process bacterial antigens for presentation by class II MHC molecules to CD4+ T-cells and by class I MHC molecules to CD8+ T-cells. Infected macrophages also release processed bacterial peptides into the extracellular medium, stabilizing empty class I MHC molecules of bystander cells. Together, we conclude that BcCVs acquire MIIC characteristics, supporting the notion that macrophages infected with B. cenocepacia contribute to establishing an adaptive immune response against the pathogen.